2021
DOI: 10.1123/kr.2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Students With Disabilities Toward Physical Education: A Review Update 2014–2019

Abstract: The purpose of this article is to review qualitative inquiries examining the perspectives of students with disabilities toward physical education (PE) published from 2014 to 2019, as an update to the 2015 review by Haegele and Sutherland. Keyword searches were used to identify articles from nine electronic databases, and seven articles met all inclusion criteria. The seven selected articles were subjected to a narrative analysis, and three thematic clusters emerged: (a) an “inconvenience”: the PE teacher’s inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
4
10
0
2
Order By: Relevance
“…In search of a deeper understanding of these relations, we identified social hierarchy as an underlying structure determining the students' perceived positioning within the social context and thus directing their feelings of being (de-)valued. Generally, the experiences reported in the interviews are closely aligned with those recalled by persons with disabilities in integrated PE settings in international contexts [35], including those with visual impairments [4,18], as well as those in previous German studies [25,26]. Interestingly, these negative experiences were not restricted to only integrated PE settings, whereas Tim, who exclusively attended special schools throughout his educational experiences, also experienced social isolation.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In search of a deeper understanding of these relations, we identified social hierarchy as an underlying structure determining the students' perceived positioning within the social context and thus directing their feelings of being (de-)valued. Generally, the experiences reported in the interviews are closely aligned with those recalled by persons with disabilities in integrated PE settings in international contexts [35], including those with visual impairments [4,18], as well as those in previous German studies [25,26]. Interestingly, these negative experiences were not restricted to only integrated PE settings, whereas Tim, who exclusively attended special schools throughout his educational experiences, also experienced social isolation.…”
Section: Discussionsupporting
confidence: 70%
“…This perhaps is most disturbingly exemplified by the stories of Carla, who experienced significant bullying by her peers which resulted in being physically endangered, who were likely influenced by the way in which her teacher viewed and treated her as unhuman. This finding, again, stems from the way her teacher treated her (as unhuman), and should perhaps be unsurprising, as prior work in this area of inquiry in different settings has demonstrated that the way in which teachers treat students with disabilities has a large influence on the way in which peers treat those same students [35].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Problematically, even at times when disabled children and young people are permitted access to activities in these settings, they are commonly relegated to passive, unimportant or tokenistic roles (Fitzgerald, 2005;Haegele, Kirk, et al, 2020). We also know that disabled children and young people are more likely to experience peer-led social isolation and bullying (Holland & Haegele, 2021) which may lead to self-harm and self-isolation (Haegele & Maher, 2021). Further, disabled children and youth people are likely to receive inappropriate support (Maher & Macbeth, 2013) and instruction (Morley et al, 2021), and have their bodies and abilities judged negatively by non-disabled peers and teachers through an ableist gaze (Haegele, Hodge, et al, 2020;Haegele, Kirk, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further, disabled children and youth people are likely to receive inappropriate support (Maher & Macbeth, 2013) and instruction (Morley et al, 2021), and have their bodies and abilities judged negatively by non-disabled peers and teachers through an ableist gaze (Haegele, Hodge, et al, 2020;Haegele, Kirk, et al, 2020). Perhaps unsurprisingly, physical education specifically is a space that many disabled young people do not experience feelings of belonging, acceptance or value, particularly in mainstream or integrated contexts (Haegele & Maher, 2021;Holland & Haegele, 2021). Of concern, the challenging experiences described by disabled children and young people in settings, like physical education, are antithetical to concepts associated with inclusion (Haegele, 2019;Spencer-Cavaliere & Watkinson, 2010) and are likely to lead to disengagement from activities outside of the classroom.…”
Section: Introductionmentioning
confidence: 99%